The gender perspective and the protection of property rights of women against divorce - Pellegrini, María Victoria (2022)
The persistence of subordinated and unequal gender relations affects women preventing them from fully enjoying their substantive right to equality. The gender- neutral language of laws can exacerbate challenges women face for their rights to be acknowledged. For that reason, gender mainstreaming constitutes an effective tool which enables adjudicators to better assess the facts and evidence of a gender-related case and thus construe laws in such a way as to adjust the structural imbalance between men and women. In recent years, courts have resorted more frequently to this tool to adjudicate cases. . However, it is still in an early face as regards the division of marital assets. For that purpose, this papers reviews, as an example, some Argentine judgments in which this approach helped restore the property rights of women.